2018
DOI: 10.1002/adfm.201706291
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Efficiency of Organic Dye‐Sensitized Solar Cells over 10.3% Using Locally Ordered Inverse Opal Nanostructures in the Photoelectrode

Abstract: 3D inverse opal (3D-IO) oxides are very appealing nanostructures to be integrated into the photoelectrodes of dye-sensitized solar cells (DSSCs). Due to their periodic interconnected pore network with a high pore volume fraction, they facilitate electrolyte infiltration and enhance light scattering. Nonetheless, preparing 3D-IO structures directly on nonflat DSSC electrodes is challenging. Herein, 3D-IO TiO 2 structures are prepared by templating with self-assembled polymethyl methacrylate spheres on glass sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…From 1, 6-bromo-4,4-bis(4-hexylphenyl)-4H-indeno [1,2-b]thiophene, 2 can be obtained via Grignard reaction and cyclization under acidic conditions. 30 Applying the same approach starting from 8 afforded compound 9. The triarylamine units 3, 4 and 10 were obtained via Buchwald-Hartwig cross-coupling reaction using unsubstituted or alkoxysubstituted diphenylamine.…”
Section: Design and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…From 1, 6-bromo-4,4-bis(4-hexylphenyl)-4H-indeno [1,2-b]thiophene, 2 can be obtained via Grignard reaction and cyclization under acidic conditions. 30 Applying the same approach starting from 8 afforded compound 9. The triarylamine units 3, 4 and 10 were obtained via Buchwald-Hartwig cross-coupling reaction using unsubstituted or alkoxysubstituted diphenylamine.…”
Section: Design and Synthesismentioning
confidence: 99%
“…This dye showed an efficiency of over 9% in DSSCs fabricated with classical architectures, and up to 10.3% with inverse opals-based electrodes. 30 Consequently, in this work, we investigate further the performance of YKP-88 and report the synthesis of four new analogue compounds whose chemical structures are tuned with the goal to shi its Internal Charge Transfer (ICT) absorption band towards lower energy wavelengths while keeping control of the energy levels of the frontier orbitals. Our objective was to prove efficient and stable dyes following this molecular concept while obtaining various colours.…”
Section: Introductionmentioning
confidence: 99%
“…26 Major accomplishments have been achieved already in photovoltaics by structuring the device with photonic crystals. [27][28][29][30] In the case of 2D photonic crystals, its periodic structure diffracts incident light and enhances the optical path within the active layer, thus rendering higher efficiencies. In this work we will provide our photodetector with a back-electrode structured as a 2D photonic crystal engineered to couple incident light to photonic modes with enhanced electric field concentration in the active medium at those wavelengths of interest for the CTS absorption effect.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of sensitizers has always been a research hotspot in the field of DSSCs, and the performance of sensitizers represented by D-π-A type structure is particularly outstanding, which has been unanimously recognized by the academic community [6][7][8]. Xu et al [9] synthesized a new sensitizer with D-π-A structure and applied it to the modified photoanode and found that the photoanode with 3D inverse opal nanostructure was more favorable to the photoelectric properties of DSSC. Huang and his collaborators [10] synthesized two novel π-conjugated moieties that could be part of π-bridge for the construction of D-π-A-configured photosensitizers for DSSC applications.…”
Section: Introductionmentioning
confidence: 99%